2007
DOI: 10.1111/j.1365-2621.2006.01314.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enzymatic cross‐linking of milk proteins on properties of ice cream with different composition

Abstract: Transglutaminase enzyme (TGase) treatment has been reported to increase the viscosity of milk and gel stiffness of yoghourt and the treatment has been suggested to replace part of the fat and proteins in dairy products. In this study, the effects of TGase on some physical, rheological and sensory properties of ice cream with different fat and stabiliser contents were studied. Five ice-cream mixes were prepared. Three of them were regular-fat mixes with 10% fat but vary in the stabiliser (0.7% and 0.2%). The ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Measurements of apparent viscosity of aged ice-cream mixes were carried out according to Metwally [21] with some modifications. Brookfield Programmable Rheometer (Model RVDV-III Ultra; Brookfield Engineering Laboratories, Stoughtm, MA, USA) was used for viscosity measurements.…”
Section: Apparent Viscositymentioning
confidence: 99%
“…Measurements of apparent viscosity of aged ice-cream mixes were carried out according to Metwally [21] with some modifications. Brookfield Programmable Rheometer (Model RVDV-III Ultra; Brookfield Engineering Laboratories, Stoughtm, MA, USA) was used for viscosity measurements.…”
Section: Apparent Viscositymentioning
confidence: 99%
“…Possibly, a large agglomeration of fat globules, casein micelles, and air bubbles occurs in ice cream studies. Metwally (2007) observed that fat is covered by a partly coalesced protein layer stabilizing the air bubbles and foam structure, which makes for better ice cream texture, avoiding large crystals formation.…”
Section: Crystals Content At 30 °C At the Presence Of Enzymesmentioning
confidence: 98%
“…In addition, it is assumed that the performance of transglutaminase formed links between milk proteins, creating a fine network that immobilized the water in large proportions and probably the same occurred with fat to form a firm gel. This causing protein hardening, covering fat globules and taking part in the protein network, creating air bubbles, which occupy spaces in the middle by avoiding water movement as a consequence, hindering large crystals formation observed in ice cream during storage (Metwally, 2007). The crystal formation occurs during the initial freezing process, and its size is critical to determine the ice cream quality.…”
Section: Crystals Content At 20 °C At the Presence Of Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…A 120-g block of ice cream sample was placed on a wire screen located on top of a beaker and allowed to melt at room temperature (22 ± 1°C). The weight of drainage recorded at 10-min intervals was plotted against time and the melting rate (g/min) was calculated from the slope of the melting chart (Elsayed Metwally, 2007).…”
Section: Short Communicationmentioning
confidence: 99%